2005
DOI: 10.1055/s-2005-837459
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Fatigue of the Knee Extensor Muscles Induced by Electromyostimulation

Abstract: The main purpose of this study was to characterise neuromuscular fatigue induced by 30 contractions of the knee extensor muscles evoked by electromyostimulation (EMS). Twelve healthy subjects were tested before and after a typical EMS session (frequency: 75 Hz, on-off ratio: 6.25 s on-20 s off) used for quadriceps femoris muscle strengthening. Surface electromyographic (EMG) activity and torque obtained during maximal voluntary and electrically evoked contractions were analysed to distinguish peripheral from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
63
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 31 publications
17
63
1
Order By: Relevance
“…3). Zory et al (2005) reported that MVC decreased approximately 20% immediately after 30 isometric contractions of the knee extensors evoked by EMS (75 Hz, on-off ratio 6.25-20 s), and neuromuscular propagation failure was mainly responsible for the decrease. It seems that excitation-contraction coupling failure was at least partially responsible for the decreases in MVC (Ingalls et al 2004); however, ultrastructural changes in myofibrils as shown in the study by Mackey et al (2008) may also account for the long-lasting decreases in MVC after EMS.…”
Section: Discussionmentioning
confidence: 97%
“…3). Zory et al (2005) reported that MVC decreased approximately 20% immediately after 30 isometric contractions of the knee extensors evoked by EMS (75 Hz, on-off ratio 6.25-20 s), and neuromuscular propagation failure was mainly responsible for the decrease. It seems that excitation-contraction coupling failure was at least partially responsible for the decreases in MVC (Ingalls et al 2004); however, ultrastructural changes in myofibrils as shown in the study by Mackey et al (2008) may also account for the long-lasting decreases in MVC after EMS.…”
Section: Discussionmentioning
confidence: 97%
“…Thus a limitation is that it is not possible to investigate any correlation between stimulation intensity and other physiological variables in this study. However, issues such as pain and (or) discomfort that are associated with application of NMES mean that it is difficult to rapidly increase intensity to produce high levels of muscle contraction force early during a session (Theurel et al 2007;Zory et al 2005). A gradual increase in intensity is required to accommodate the current.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant compound muscle action potential (M wave) and the maximal mechanical twitch response (peak twitch force, Pt) are recorded. A reduction in M-wave amplitude is interpreted as evidence of impaired neuromuscular transmission or action potential propagation (BiglandRitchie et al 1982) and if Pt is reduced to a comparable extent, this probably indicates that the impaired force production is due to reduced muscle excitability (Zory et al 2005). However, it should be noted that action potentials in muscle cells might have a large safety margin so that their amplitude can be greatly reduced before Ca 2?…”
Section: Introductionmentioning
confidence: 97%